Investigation into the optimal fleet employment strategy with concentration on the supramax bulk carrier east of Suez market (volume three) - Tay, Yu Xing (2014)
Part Three of the research report will focus on the process of determining the optimal portfolio mix for a ship-owner with 10 Supramax bulk-carriers trading east of Suez from the period of 2006 to 2012. An optimal portfolio has been defined as one that creates the highest amount of returns at the lowest amount of risks. The optimality of a particular portfolio is directly affected by the ship-owner’s choice of acquisition methods and employment strategies.